Influence of herbicides on the formation of valuable agronomic traits of sunflower: a review of modern research (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Abstract. The article summarizes current scientific approaches to assessing the impact of herbicides on the formation of economically valuable traits in sunflower, which is one of the leading oilseed crops in Ukraine and worldwide. The relevance of the study is determined by the need to improve the efficiency of sunflower production under conditions of increasing anthropogenic pressure, the spread of herbicide-resistant weeds, and the potential negative effects of chemical plant protection products on crop growth, development, and productivity. Despite the high efficacy of herbicides in weed control, their application may be accompanied by manifestations of phytotoxicity, which limits the realization of the genetic potential of sunflower hybrids. The purpose of the study was to generalize and systematize literature data on the effects of herbicides on the physiological and biochemical processes, morphological traits, growth and development of sunflower plants, as well as on the formation of yield structure components and the overall productivity of the crop. Results. The analysis showed that herbicides exert their effects through the inhibition of key biochemical processes, including photosynthesis, amino acid synthesis, fatty acid synthesis, and cell division, resulting in alterations in plant morphogenesis. It was found that herbicide effects may manifest as chlorosis, necrosis, leaf deformation, growth suppression, reduced biomass accumulation, and impaired root system development. It was demonstrated that the degree of phytotoxicity depends on the type of herbicide, application rate, crop growth stage, weather conditions, and sunflower genotype. Herbicides were also found to significantly affect yield structure components, particularly plant stand density, head diameter, seed number, and thousand seed weight, which ultimately determine the final yield level. Conclusions. The generalized findings indicate that, alongside their positive role in weed control, herbicides may cause substantial yield losses if application regulations are not properly followed. In this regard, the need to optimize herbicide load, introduce herbicide-tolerant hybrids, and implement integrated weed management systems is well justified. Therefore, the rational use of herbicides is an important prerequisite for increasing sunflower productivity and ensuring the ecological safety of agrocenoses.
Keywords: sunflower; herbicides; phytotoxicity; yield; weed control; plant growth and development